Tattersall, The World From Beginnings To 4000 BCE - Lam, Elizabeth (Teaching History: A Journal of Methods, 2009)
Human evolution is defined as both the biological and cultural development of humans. Ever since the existence of scientific research, human evolution has been a central topic in the crossfire of scientific fields such as physical anthropology, linguistics, and genetics. Through the examinations done in paleoanthropology, we know today that human beings evolved from the homo sapiens species. Thanks to the results achieved in studying human origins and species, we are nowadays able to estimate that the history of human evolution began more than 4,000 years ago. This complex history of human evolution is the topic of Ian Tattersall’s The World From Beginnings to 4000 BCE. In an effort to provide a comprehensive, thoroughly readable overview of the "new world history," Tattersall’s work is the first volume in the series The New Oxford World History published by Oxford University Press.